A Collect of Recommendations and Guidelines for Management and Treatment of Underlying Malignancies During the COVID-19 Pandemic - Mojgan Karimi-Zarchi; Soheila Sayad; Mohammad Vakili; Ahmad Shirinzadeh-Dastgiri; Amirhossein Naseri; Mohammad Hossein Antikchi; Sepideh Azizi; Kazem Aghili; Hossein Neamatzadeh; Elahe Akbarian (Acta Medica Iranica, 2024)
The coronavirus disease 2019 (COVID-19) pandemic is the main challenges to public health systems worldwide now. Cancer patients are considered as a high risk group during the COVID-19 pandemic. Considering the evidence so far, cancer as underlying comorbidities might increase the risk of death in patients with COVID-19. Many cancer patients with increased risk of contracting COVID-19 than the general population regularly visit health facilities for treatment and disease surveillance. Thus, the COVID-19 pandemic has a profound impact on cancer care and treatment. Here, we attempted to summarize the current suggestions for handling of cancer patients during COVID-19 pandemic. We carried out a integrative literature review using several online bibliographies. A total of 113 papers were accessed for the time frame between October 05 2020 and October 10 2020. After screening of titles and full-texts, 10 publications were selected in this study. In this work some recommendations and guidelines that would help for management and treatment of cancer for the purpose of address the challenges during COVID-19 pandemic were collected. We hope that this collection recommendations and guidelines assist health care providers in management of individuals with underlying malignancy during the COVID-19 pandemic.